2006
DOI: 10.1016/j.jhsb.2005.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Hand Replantations Following Complete Amputations at the Wrist Joint: First Experiences in Hanoi, Vietnam

Abstract: Five completely amputated hands at the level of the wrist joint were replanted. The five patients were all men, ranging from 19 to 31 years and the amputations were all the result of knife injuries. All the revascularizations were successful. Secondary tenolysis was required in one case. Postoperative functional results compared to the uninjured hand were evaluated according to five main criteria: (1) the patient's overall satisfaction with the hand; (2) recovery of flexor and extensor function of the thumb an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…The aim of hand replantation is to restore function and appearance, regain sufficient sensation for the performance of normal daily tasks and allow patients to return to their previous employment [6][7][8][9][10] Although technological advances over the past three decades have resulted in hand replantations becoming a routine procedure in reconstructive microsurgical centres around the world, reports of results following hand replantation at the level of the wrist joint are uncommon. In a multi-institutional retrospective study from Shanghai, Louisville and Zurich in 1985, Meyer [11] reported excellent and good post-operative functional results (Grade I and II) in 81% of hand replantations just proximal to the wrist joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of hand replantation is to restore function and appearance, regain sufficient sensation for the performance of normal daily tasks and allow patients to return to their previous employment [6][7][8][9][10] Although technological advances over the past three decades have resulted in hand replantations becoming a routine procedure in reconstructive microsurgical centres around the world, reports of results following hand replantation at the level of the wrist joint are uncommon. In a multi-institutional retrospective study from Shanghai, Louisville and Zurich in 1985, Meyer [11] reported excellent and good post-operative functional results (Grade I and II) in 81% of hand replantations just proximal to the wrist joint.…”
Section: Discussionmentioning
confidence: 99%
“…The post-operative functional results were evaluated using five main criteria: [5,6] 1. The recovery of flexor [Tables 1 and 2 and Figures 4-7] and extensor mobility by the thumb and fingers.…”
Section: Assessmentmentioning
confidence: 99%
“…Best results are achieved when the injury is a cutting injury at the level of the wrist. 38 However, in Case 2, the injury was a mixed pattern with elements of laceration, crush and traction/avulsion. Further complicating the case was the multilevel nature of the injury.…”
Section: Discussionmentioning
confidence: 96%
“…Familiarity with the anatomy around the wrist, especially the arrangement of tendons, is the key to performing a successful replantation. Although some authors suggest removal of the FDS tendons of the digits to avoid tendon adhesion between it and the flexor digitorum profundus (FDP) tendons (Hoang, 2006), we prefer to repair all the tendons and simultaneously release the flexor retinaculum ligament, overlying the carpal tunnel, to prevent adhesion and tightness within the tunnel. Initially, all the tendons are repaired, as possible.…”
Section: Handmentioning
confidence: 99%